Adding China to the Global Projection Model - Blagrave, Patrick (IMF Working Papers; Working Paper ;, 2013)
We extend the Global Projection Model (GPM) to include a separate block for China. China plays an important role in shaping global economic outcomes, given its sheer size and trade integration with other key economies, its demand for commodities, and its policies. Also, the Chinese economy has several unique features which differentiate it from the rest of emerging Asia. These features (the use of multiple monetary-policy instruments and a managed-floating exchange-rate policy) mean that a separate treatment of China allows for a better consideration of China, as well as how the rest of emerging Asia behaves.